The roles, works, and skills of paraprofessionals in academic libraries of South Manila Educational Consortium (SMEC), Mendiola Consortium, and European Studies Consortium in the Philippines - Cauilan, Bob P.; Apolinario, Rhea Rowena U. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2015)
The study determined the roles, skills and tasks/works of the paraprofessional staff of the member libraries of the South Manila Educational Consortium (SMEC), Mendiola European Studies Consortium and Mendiola Consortium. It compared the existing roles, works, and skills of the paraprofessionals against those specified in the PAARL standards and RA 9246. The population included all paraprofessional staff currently employed in the member academic libraries of the three consortia through total enumerations with two hundred five (205) paraprofessionals of the member libraries of the three consortia as respondents of the study.
The study revealed that the respondents are mostly 41-45 years old, males, and bachelor's degree graduates and have varying specializations. In addition, majority of them are clerks or support staff stationed at the Readers' Services Section and receive a monthly salary of Php 15,000-19,999. Moreover, the paraprofessionals have rendered 1-5 years of service in their workplaces, are occupying permanent positions and have attended seminars/training which are national in scope. Their roles include : processing fines, reserve, checking in/checking out of library materials, teaching internet navigation, online searching and how to use the OPAC, and answering ready reference or directional queries. On the overall mean, the enumerated roles of the paraprofessional staff garnered 2.36 which mean that collectively, they perform the enumerated roles "Rarely". In terms of the skills, they have shown an ability to search, locate and use instructional materials, ability to determine accuracy, currency, and relevance of information, and ability to communicate, establish interpersonal relations and apply reference interview techniques to library users. A "neutral" rating was garnered on the skills of the paraprofessional staff in the three consortia. In task characteristics, an "often" description was given to the paraprofessionals' decision-making autonomy, work methods, task variety, feedback from job, information processing, problem solving, skill variety, specialization, social support, ergonomics, work conditions, equipment use and on the overall rating. This connotes that the paraprofessionals frequently do the tasks considered in the study.
Even if the paraprofessionals of the three consortia are working in more than one section, the ratio of the professional librarians and library staff are found to be still within the PAARL standards. They were also found to be doing technical service and reader services (reference/circulation work) which show that they are doing roles and tasks stipulated in RA 9246 that only librarians should be doing. The practice of having a continuing staff development program in the three consortia is an attestation that the agencies are mindful of the professional development of the paraprofessionals as mandated in the PAARL standards but development programs that concentrate on enhancing their 21st century skills were recommended in the study.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Library technicians -- Philippines -- Manila; Library cooperation -- Philippines -- Manila -- Evaluation; Academic libraries -- Philippines -- Manila